Uma mãe nova ou uma nova mãe?: um estudo sobre os sentidos da maternidade para as mulheres a partir dos 35 anos. - Costa, Ana Cláudia Alexandre Carneiro da (2024)
Many women postpone their pregnancies until “older” ages. Regarding this reality, the Ministry of Health, in its High-Risk Pregnancy Manual, defined advanced maternal age (AMI) as the pregnancy of women aged 35 or over. In the last 30 years, worldwide, birth rates have been decreasing, however the number of pregnancies in women aged 35 and over has been increasing at a faster rate than in any other age group. Starting from this context, the research that supported this thesis had as its problem question: would pregnancy at an advanced maternal age, and all the possible difficulties linked to it, really be an option for women as a result of their “empowerment” and, consequently, female decision-making “power”? When reflecting on this issue and thinking about the social pressure that women suffer in relation to being mothers, we can question whether these pregnancies in IMA are configured as a decision or as another form of “imposition”, a social direction, a way of “demand” made in order to make women “fulfill” what is expected of them biologically and socially: to procreate. From this perspective, our general objective was: to understand the meanings of motherhood for women with advanced pregnancy. And, as specific: map the discourses constructed around motherhood at an advanced age; mapping the field of social, biomedical and psychological forces that women who become pregnant at an advanced age go through; and analyze the subjective constructions built from this field of forces. Our methodological approach was based on the qualitative bias of the cartographic approach, using the script for information on the participants' sociodemographic data, the narrative interview and the field diary as means to get to know and get in touch with the five women who participated in this research. The results demonstrated that there is no single meaning that explains what leads a person to become a mother after the age considered “safe” by medicine for mothering, including that having a child after the age of 35 would not be an option, but the moment of the life each of them achieved to give birth. And so, meanings were found linked to everything from the dream of becoming a mother, regardless of how many years of life you already have, to the concern with social demands for delays in getting pregnant. It was also possible to identify that, along with the reality of having a child in IMA, there was a concern about solving important aspects, for example, the lack of a partner, marriage and financial conditions that would give security to get pregnant and, also, acceptance of the use of technology, such as: egg freezing and artificial insemination to have a child. Psychology benefits from discussing this topic by opening up space to “listen to women's voices” and providing environments for social, academic reflection and scientific research, so that female needs increasingly gain strength and women build powerful lines of escape. enough to go against the strict social lines that decide on their bodies.